The future of fish drying technology in Barangay Agtongo, Romblon, Romblon a technology road map report - Mateo, Robeson San Diego (University of the Philippines Diliman, 2011)
This paper aims to construct a 3-year Technology Road Map of the fish drying practices and technology of Barangay Agtongo, province of Romblon, Romblon. In an attempt to chronicle their existing fish drying practices, the road map will be a necessity to better understand and recommend specific technologies that can be adapted and acquired by the said community. A technology roadmap may be defined as a plan that links the short and long-term goals of a firm or community, with specific technology solutions to help meet those goals (Garcia and Bray, 1997). The said plan can be applied to a new product or process, or in relation to the acquisition and assimilation of technologies that may be new to the firm or community. A technology road-map has several uses. It may be employed to help reach a consensus about a set of needs and the technologies required to satisfy those needs. A technology roadmap can also provide a mechanism to help forecast technology developments. Likewise, the technology road-mapping process can provide a framework to help plan and coordinate technology developments, based on the overall business and technology strategies of firms, organizations, and communities moving forward. Barangay Agtongo in Romblon, Romblon has been engaged in fish drying activities which is its people's main source of food and livelihood. Though the palatability of dried fish produced by the community is superior compared to the locally available commercial variants, the said end-product from Agtongo doesn't keep long. Aside from this, their production process technology and capability is so crude, that it affects the potential margins of the community due to inefficiencies related to their existing production process, such as production wastes, rejects and end-product spoilage. With the use of the technology road-mapping process, several technologies were identified according to the current needs of the said Barangay. The said technologies were derived from the community's existing fish drying practices and technology, as well as its current and potential markets. Inter-relationships between the perceived technologies and the incremental innovations that can be introduced in order to address specific practices were also identified accordingly. Furthermore, these interrelationships were analyzed by combining the results of an Environmental Scan done within the said community, and the inputs and plans of SIKAT, in the hopes of developing specific programs baed on the said technologies. The said activity was conducted in line with SIKAT's goal of providing continuous sustenance for the community during the rainy season, as well as a more reliable livelihood source, given the abundance of aquatic resources in the said vicinity.